Madrasah-Based Management: Quality Improvement Strategies in Madrasah - Susanto, Susanto (JURNAL AL-TANZIM, 2022)
This study explores quality improvement strategies in Madrasahs in the Ponorogo district during the Covid-19 situation. This research is quantitative research with a descriptive method. The population in this study were educators and education staff in Madrasah, Ponorogo Regency, amounting to 15 madrasah. The research analysis was done descriptively. This study found that the madrasa-based quality improvement strategy developed in Ponorogo Regency during the Covid-19 pandemic; First, the planning aspect, namely curriculum adjustments, online-based learning services, administrative services, and adjustments to the rules according to the Covid-19 situation policy. Second is the development of intelligent system innovation. Third, ensure that educators and education personnel carry out their duties according to health protocols and increase capacity according to learning needs in the Covid-19 situation; Fourth, aspects of parental support, provision of parental consultation rooms, and essential skills. The implications of the research findings can be a positive inspiration for improving the quality of madrasah in the Covid-19 pandemic.